Edukasi Zat Aditif Makanan Berbahaya dan Analisa Boraks Menggunakan Kunyit Di Tlogomas, Lowokwaru, Malang - Khoiroh, Lilik Miftahul; Kartika, Siskaela; Hanapi, Ahmad (Universitas Muhammadiyah Sukabumi, 2024)
Borax is a hazardous chemical that is often used as a food additive, although its use has been banned in many countries, including Indonesia. Consumption of borax can cause cancer, kidney failure, liver disorders, reproductive system disorders, central nervous system disorders, and immune system disorders. Irresponsible manufacturers often add borax to meatballs, noodles, tofu, and crackers to make them chewier and last longer. Turmeric contains curcumin, which functions to break down the borax bond into boric acid and bind it into a reddish-brown rosocyanin chelate complex. The purpose of this community service program is to provide education about hazardous food additives, the characteristics of foods containing borax, the impact of borax consumption on health, and training on how to analyze borax using turmeric in Tlogomas, Lowokwaru, Malang. Education is carried out using lecture methods, discussions, demonstrations, and training on analyzing borax. It has been proven that this activity can increase participants' knowledge and skills in identifying borax in food by up to 92%.